The Concept of International Treaty and Their Role in The System of International Relations - Mahmatkulova Saida Ilhom qizi (Zien Journals, 2022)
This article defines the concept of international law, its features and the essence of their content, the subject of international law; the concept of sources of law of international agreements; entry into force, promulgation and registration of international agreements; allows for a detailed study and identification of their species.
Keywords: study; defines; international; essence